Etomidate in the management of hypercortisolaemia in Cushing's syndrome: a review. - Preda, V; Sen, J; Karavitaki, N; Grossman, AB (2012)
This review addresses the practical usage of intravenous etomidate as a medical therapy in Cushing's syndrome. We reviewed the relevant literature, using search terms 'etomidate', 'Cushing's syndrome', 'adrenocortical hyperfunction', 'drug therapy' and 'hypercortisolaemia' in a series of public databases. There is a paucity of large randomised controlled trials, and data on its use rely only on small series, case study reports and international consensus guideline recommendations. Based on these, etomidate is an effective parenteral medication for the management of endogenous hypercortisolaemia, particularly in cases with significant biochemical disturbance, sepsis and other serious complications such as severe psychosis, as well as in preoperative instability. We suggest treatment protocols for the safe and effective use of etomidate in Cushing's syndrome.